Prevalence of insomnia among university students in Saudi Arabia: a systematic review and meta‑analysis - Mohamed Baklola; Mohamed Terra; Mohamed Al-barqi; Yaqeen Hasan AbdulHusain; Sohaila Ahmed Asiri; Norah Saad Jadaan; Ali Haroona; Sayed Almosawi; Sarah Saud Al Ahmari (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Insomnia is a prevalent sleep disorder affecting cognitive functions critical to academic performance. University students, particularly in high-stress academic settings, are highly vulnerable. Despite its significant impact on students' health and education, there is limited research on the prevalence of insomnia among university students in Saudi Arabia. This systematic review and meta-analysis aim to assess the prevalence of insomnia among university students in Saudi Arabia, focusing on demographic variations and academic settings, to provide evidence for targeted interventions. Methods A comprehensive literature search was conducted across databases including PubMed, Scopus, and Web of Science, with additional manual searches. Inclusion criteria were cross-sectional studies addressing insomnia prevalence among Saudi university students, using standard diagnostic criteria. A total of 11 studies met the inclusion criteria, comprising data from diverse faculties, including medical and non-medical disciplines. Quality assessment was conducted using the Newcastle-Ottawa Scale. Statistical analyses were performed using a random-effects model to account for heterogeneity. Results Eleven studies, involving a total of 8297 university students, were included in the analysis. Insomnia prevalence varied widely, ranging from 19.3% to 98.7%, with a pooled prevalence of 43.3% (95% CI 28.9–58.2%). Subgroup analyses showed a prevalence of 38.6% among medical students and 38.7% among female students. The analysis revealed high heterogeneity (I 2 = 99.17%), indicating significant variability in study designs, populations, and diagnostic methods. Conclusions Insomnia is highly prevalent among university students in Saudi Arabia, with significant variations across demographics and academic contexts. The findings underscore the urgent need for targeted interventions, including stress management, improved sleep hygiene education, and support systems to mitigate the impact of insomnia on academic performance and overall health. Future research should explore the longitudinal impacts of insomnia and the efficacy of tailored interventions in this population.